Transcriptome analysis of Carica papaya embryogenic callus upon De-etiolated 1 (DET1) gene suppression - Diyana Jamaluddin; Normah Mohd Noor; Hoe-Han Goh (Genomics Data, 2017)
Papaya is considered to be one of the most nutritional fruits. It is rich in vitamins, carotenoids, flavonoids and other phytonutrient which function as antioxidant in our body [1]. Previous studies revealed that the suppression of a negative regulator gene in photomorphogenesis, De-etiolated 1 (DET1) can improve the phytonutrient in tomato and canola without affecting the fruit quality [2,3]. This report contains the experimental data on high-throughput 3′ mRNA sequencing of transformed papaya callus upon DET1 gene suppression.